DFT study of the structural, electronic, and optical properties of bulk, monolayer, and bilayer Sn-monochalcogenides - Attia Batool; Youqi Zhu; Xilan Ma; Muhammad Imran Saleem; Chuanbao Cao (Applied Surface Science Advances, 2022)
Tin monochalcogenides (SnSe, SnS), with advantages of earth abundance, environmental friendly, chemical stability, and less toxicity can be used in Li-ion batteries, piezoelectric, optoelectronics, sensors, and thermoelectric. Here, we used the ultra-soft pseudo-potential technique depending on density functional theory with generalized gradient approximation (GGA) to calculate the electronic, optical, and structural properties by changes related to the reduction of dimensionality from bulk to monolayer or bilayer structure. The calculated parameters show that the bandgap energies of SnS and SnSe semiconductors (0.5∼1.25 eV) cover the broadband range, and their static dielectric constant confirms the isotropic nature. We compare our theoretical results of different approximations with previously reported DFT-based and experimental results. The calculations of tin monochalcogenides show that as thickness increases, isotropic behavior increases, and material becomes crystalline. This method opens a new window to deeply understand monochalcogenide's structural, optical, and electronic properties for numerous applications, like thermoelectric, photovoltaic, and energy storage devices.